Structural evolution and vorticity of flow during extrusion and exhumation of the Greater Himalayan Slab, Mount Everest Massif, Tibet/Nepal: Implications for orogen-scale flow partitioning - Jessup, M; Law, R; Searle, M; Hubbard, MS (2006)
The Greater Himalayan Slab (GHS) is composed of a north-dipping anatectic core, bounded above by the South Tibetan detachment system (STDS) and below by the Main Central thrust zone (MCTZ). Assuming simultaneous movement on the MCTZ and STDS, the GHS can be modelled as a southward-extruding wedge or channel. New insights into extrusion-related flow within the GHS emerge from detailed kinematic and vorticity analyses in the Everest region. At the highest structural levels, mean kinematic vorticity number (Wm) estimates of 0.74-0.91 (c. 45-28% pure shear) were obtained from sheared Tethyan limestone and marble from the Yellow Band on Mount Everest. Underlying amphibolite-facies schists and gneisses, exposed in Rongbuk valley, yield Wm estimates of 0.57-0.85 (c. 62-35% pure shear) and associated microstructures indicate that flow occurred at close to peak metamorphic conditions. Vorticity analysis becomes progressively more problematic as deformation temperatures increase towards the anatectic core. Within the MCTZ, rigid elongate garnet grains yield Wm estimates of 0.63-0.77 (c. 58-44% pure shear). We attribute flow partitioning in the GHS to spatial and temporal variations that resulted in the juxtaposition of amphibolite-facies rocks, which record early stages of extrusion, with greenschist to unmetamorphosed samples that record later stages of exhumation. © The Geological Society of London 2006.